Bioaccumulation of heavy metals in Nile tilapia Oreochromis niloticus (Linnaeus 1758) fed with commercial fish feeds (Bangladesh Journal of Scientific Research, 2017)
The study was carried out to determine the concentration of heavy metals in some commonly used commercial fish feeds and to observe the bioaccumulation of Cr, Cu, Cd and Ni in liver, muscle and gills of tilapia Oreochromis niloticus after culturing them for 60 days by feeding those commercial feeds. The study revealed that the concentration of Cu was the highest (65.08 mg/kg) in handmade feed (B1) among four heavy metals. The concentrations of Cr in collected feeds were 1.75 to 3.04 mg/kg, which exceeds the permissible limit set by FAO. In cultured tilapia, the concentrations of studied heavy metals were found higher than initial concentration in fish feeds and in tilapia fingerlings. Metal levels in cultured fish followed the ranking of Cu>Cr>Ni>Cd and order in individual organs was liver>gill>muscle. The highest concentration of Cu (72.86 mg/kg) was found in liver given S feed and the lowest concentration (0.67 mg/kg) was in muscle receiving Q feed. Bioaccumulation of Cr was the highest (23.95 mg/kg) in liver taken B1 feed and the lowest (9.29 mg/kg) in muscle of tilapia cultured with C feed. Concentration of Cu exceeded the tolerable limit in fishes cultured with S and C feeds. But Cr concentration surpassed the allowable limit in every feed studied. The concentrations of Ni and Cd were below the permissible range approved by FAO. Considering the present study, tilapia cultured with these experimental feeds is not safe for human consumption. Higher concentration of these heavy metals exceeding allowable limit may cause harmful effect on human body after consumption of those fishes and can create cancer and other diseases in human body.Bangladesh J. Sci. Res. 29(2): 89-99, December-2016